KINERJA KARYAWAN DALAM KAJIAN MULTIFAKTORIAL: MEMAHAMI ASPEK DETERMINAN DALAM PERSPEKTIF YANG BERBEDA - Ati Chandrasari; Muhammad Abdullah; Eko Oby Purwanto; Ratna Puspita; Andri Rizko Yulianto (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to gain a deeper understanding and conduct empirical analysis of the impact of compensation, work discipline, and job satisfaction on the performance of A Grosir Subang employees. The chosen research method involves quantitative analysis and utilizes non-probability sampling, specifically saturated sample (census), to minimize bias and generate hypotheses effectively. Data quality testing is performed through validity and reliability testing mechanisms. Furthermore, this research includes classical assumption testing stages such as normality testing, heteroscedasticity testing, and multicollinearity testing, followed by hypothesis testing and multiple linear regression analysis. The findings of this study demonstrate that individual variables, namely work discipline, job satisfaction, and compensation, positively influence employee performance. Simultaneously, when considered together, these variables also positively impact employee performance.